Pharyngoesophageal Suturing Technique May Decrease the Incidence of Pharyngocutaneous Fistula following Total Laryngectomy - Mahmut Deniz (Surgery Research and Practice, 2015)
Objectives. A pharyngocutaneous fistula (PCF) following total laryngectomy is associated with increased morbidity and severe life threatening complications. We aimed to review our experience with the PCF following total laryngectomy and determine the impact of previously reported risk factors on the development of PCF in our patients. Methods. The medical records of 20 patients who had a total laryngectomy operation were retrospectively analyzed. The association between the proposed risk factors and the incidence of the PCF was investigated. Results. Comparison of the suture techniques used for the closure of the pharynx (either continuous Cushing type or interrupted) yielded that primary interrupted sutures had a significantly higher incidence of PCF formation (p<0.05). Although it was not statistically significant, diabetes mellitus was also associated with increased PCF formation (p>0.05). No significant difference was observed between the PCF and non-PCF groups in terms of other proposed risk factors (p>0.05).  Conclusions. The main risk factor associated with PCF was found to be the type of pharyngeal closure technique. A vertical closure with a Cushing type continuous suture may be more successful than interrupted sutures in preventing a PCF.